The dynamics of biodiversity structure of soil microorganisms under the impact of biopreparations during potato growing season - Patyka, M. V.; Borodai, V. V.; Khomenko, E. V.; Patyka, V. P. (Acta Agraria Debreceniensis, 2016)
The use of biological preparations such as Phytotsid and Planryz contributes the increase of the general number of soil bacteria population by 13.0–36.1% in the case of potato variety Scarbnytsya and by 4.5–24.6% for potato variety Oberig compared with control. It also increases the number of saprophyte microflora, which compete with plant pathogens, micromycetes, and causes 1.2–1.8 times reduction in the number of soil fungi – Fusarium and Alternaria. During the application of Rovral Akvaflo the Shannon ecological index of species biodiversity is lower than during the biopreparation use. The decrease of species biodiversity was observed as well as strengthening the dominance of some species (dark pigmentation in fungi).